Comparison of the Effectiveness of Warmed Versus Room Temperature Intravenous Fluids Administration to Prevent Intraoperative Heat Loss in Anaesthetised Calves Undergoing Umbilical Herniorrhaphy - Sitkican Okur; Latif Emrah Yanmaz; Mumin Gökhan Senocak; Ayse Golgeli; Ferda Turgut; Omer Tarik Orhun; Yakup Kocaman; Ugur Ersoz (Veterinary Medicine and Science)
ABSTRACT Background Warmed intravenous (IV) fluids administration to prevent hypothermia provide controversial results in humans, cats and dogs, but its effect on calves is unknown. Objectivxe To evaluate the effectiveness of warmed IV fluids administered to prevent intraoperative heat loss in anaesthetised calves undergoing umbilical herniorrhaphy. Methods Thirty Simmental breed calves (aged 10–30 days) were randomly divided between two equal groups, wherein the infusion fluid (Ringer's lactate, 5 mL/kg/h) was administered either at room temperature (Group RoT) or warmed (Group WF). Pulse rate (PR), respiratory rate (fR), peripheral haemoglobin oxygen saturation (SpO2) and rectal temperature (RT) were recorded immediately after the onset of anaesthesia induction (T0) at T5, T10, T15, T30, T45 and T60. Duration of anaesthesia, surgery time and recovery scores were also noted. Results The PR, RT and fR values showed no significant difference between groups over time (p > 0.05). There was no significant difference in duration of anaesthesia, surgery time or recovery score between groups (p > 0.05). Conclusions The findings of the current study suggest that warmed IV fluid as the warming method did not prevent intraoperative hypothermia in calves. A constant‐rate infusion of warmed fluid (5 mL/kg/h) is insufficient to prevent intraoperative hypothermia in calves.